Phytochemical Profiling, Antimicrobial, and Antioxidant Activities of Tamarindus indica Pulp Extracts: A Comprehensive Evaluation - Mohamed, Nidal Eisa Abdalla; Ismail, Ayman A. A.; Eisa, Alaa (Biology, Medicine, & Natural Product Chemistry, 2025)
The study looks at the antioxidant, antibacterial, and phytochemical characteristics of pulp extracts from Tamarindus indica. Several solvent fractions were obtained from the extraction process, such as hexane, butanol, ethyl acetate, crude, and aqueous, all of which indicated the existence of primary and secondary metabolites. High amounts of flavonoids, alkaloids, tannins, saponins, and steroids were found by phytochemical screening, especially in the butanol and ethyl acetate fractions. With an inhibition zone of 17 mm against Bacillus subtilis, the ethyl acetate extract had the most excellent antibacterial activity in antimicrobial tests conducted using the cup-plate agar diffusion method. With a radical scavenging activity of 11 ± 0.1%, the crude extract's antioxidant activity was found to be modest, in contrast to the positive control's 87% activity, propyl gallate (PG). These findings show that T. indica extracts have a promising antibacterial potential, despite their still-low antioxidant efficiency. According to the research, T. indica may be a valuable source of bioactive substances for medical and pharmacological uses, especially in the treatment of infections.